2012
DOI: 10.1080/03650340.2010.530254
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bulk density of waterlogged soils from basic properties

Abstract: Pedotransfer functions (PTFs) to predict bulk density (BD) from basic soil data are presented. Available data pertaining to seasonally impounded shrink-swell soils of Jabalpur district in the Madhya Pradesh state of India were used for the study. The data included horizon-wise information of 41 soil profiles in the study area covering nearly 5 million ha. Six independent variables, namely textural data (sand, silt and clay), field capacity (FC), permanent wilting point (PWP) and organic carbon content (OC) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…This finding was consistent with the result of ANN reported in other studies (e.g., Motaghian and Mohammadi, 2011;Patil and Chaturvedi, 2012). Patil and Chaturvedi (2012) found that the overall performance of ANN-built PTF was better than that of MLR-built PTF. Compared with MLR, ANN had a high capability for modeling complex problems.…”
Section: Estimation Of Wal Indicessupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was consistent with the result of ANN reported in other studies (e.g., Motaghian and Mohammadi, 2011;Patil and Chaturvedi, 2012). Patil and Chaturvedi (2012) found that the overall performance of ANN-built PTF was better than that of MLR-built PTF. Compared with MLR, ANN had a high capability for modeling complex problems.…”
Section: Estimation Of Wal Indicessupporting
confidence: 93%
“…MLR is a traditional PTF development method that is widely used in soil studies (Motaghian and Mohammadi, 2011;Patil and Chaturvedi, 2012). ANN can be used to describe the systems without assumed model structure (Motaghian and Mohammadi, 2011).…”
Section: Pedotransfer Function (Ptf) Developmentmentioning
confidence: 99%
“…This implies that soils were permeable, well-aggregated, loose, and rich in organic matter. Patil and Chaturvedi (2012) observed similar outcomes in soil from the M.P. district of Jabalpur.…”
Section: Resultssupporting
confidence: 61%